Assessment of forest fragmentation in the REDD+ priority zones using two land use/land cover (LULC) sources in the tropical Andean landscape of Ecuador - Juan Paredes; Jin Kyoung Noh; Nikolay Aguirre; Yeo-Chang Youn; Pablo Cuenca (PLoS ONE, 2026)
Human-driven deforestation and fragmentation are major threats to global biodiversity and climate stability, particularly in the Amazon rainforest. Ecuador, located in the Andes–Amazon transition zone, hosts some of the world’s most biodiverse ecosystems. The REDD+ initiative, the main international mechanism for mitigating forest degradation, has identified six priority conservation areas in Ecuador—87% of which are in the Amazon region and distributed across three zones: northern, central, and southern. This study evaluates landscape fragmentation in REDD+ priority zones of the Ecuadorian Amazon over a 32-year period (i.e., 1990–2022) using a dual approach: statistical analysis with FRAGSTATS v4 and spatial modeling with Guidos Toolbox v2. Two land use/land cover (LULC) datasets were compared—one from Ecuador’s Ministry of the Environment and the other from the MapBiomas Ecuador initiative. Results revealed an overall increase in fragmentation, including a higher number of forest patches, greater isolation, and reduced patch size and representativeness. Spatial analysis indicated a clear fragmentation pattern along the north–south E45 highway corridor, which increasingly separates Andean and Amazonian ecosystems. The northern and southern zones were the most affected, due to increased accessibility linked to oil and mining activities, respectively. MapBiomas data more effectively captured fragmentation associated with small-scale deforestation. These findings provide a critical baseline for policymakers to design strategies aligned with REDD+ goals and to develop targeted actions to reduce forest fragmentation and deforestation in the Ecuadorian Amazon.